2015
DOI: 10.1002/2015ja021799
|View full text |Cite
|
Sign up to set email alerts
|

West wall structuring of equatorial plasma bubbles simulated by three‐dimensional HIRB model

Abstract: Plasma density depletions in the equatorial ionosphere, or so‐called equatorial plasma bubbles (EPBs), are generated in the postsunset period and tend to have a very complex spatial structure. Especially, the east‐west asymmetry of EPBs has been reported by various observations. Using a high‐resolution bubble (HIRB) model, which is a newly developed three‐dimensional numerical model for the equatorial ionosphere, small‐scale structuring at the west wall of large‐scale F layer upwelling is clearly reproduced fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…That is, stronger GW activity may not always lead to more EPBs, at least for GWs in this study with horizontal scales below 620 km. This implication is in line with the works of Burke et al [2004], Kudeki et al [2007], and Yokoyama et al [2015], who found that instead of gravity waves, other factors like the magnetic declination, strong zonal winds, or vertical shear of zonal plasma drift can play more important roles in controlling EPB occurrence. Notably, the seasonal variation of the zonal wind in the evening sector fits perfectly to that of the EPB, with strongest wind around equinoxes, and weakest wind around June solstice [Liu et al, 2016].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…That is, stronger GW activity may not always lead to more EPBs, at least for GWs in this study with horizontal scales below 620 km. This implication is in line with the works of Burke et al [2004], Kudeki et al [2007], and Yokoyama et al [2015], who found that instead of gravity waves, other factors like the magnetic declination, strong zonal winds, or vertical shear of zonal plasma drift can play more important roles in controlling EPB occurrence. Notably, the seasonal variation of the zonal wind in the evening sector fits perfectly to that of the EPB, with strongest wind around equinoxes, and weakest wind around June solstice [Liu et al, 2016].…”
Section: Discussionsupporting
confidence: 88%
“…Medium-scale gravity waves (GWs) with horizontal scales of a few hundred kilometers in the bottomside F region have been frequently suggested to play a key role in EPB seeding [e.g., Fritts et al, 2008;Abdu et al, 2009]. However, there are also a body of studies that argue against this hypothesis [e.g., Kudeki et al, 2007;Yokoyama et al, 2015]. The lack of direct measurements of gravity waves at this critical altitude undoubtedly contributes to this debate.…”
Section: Introductionmentioning
confidence: 99%
“…Applying multiple seeding components and an eastward neutral wind, east-west asymmetry, and tilted structures can also be reproduced, as shown in Fig. 8 (Yokoyama et al 2015). Although the outline of tilted EPBs is similar to the previous 2D model, result shown in Fig.…”
Section: Three-dimensional Modelssupporting
confidence: 50%
“…The most recent models developed by the author and colleagues could reproduce very turbulent structures inside EPBs (Yokoyama et al 2014(Yokoyama et al , 2015Yokoyama and Stolle 2017;Rino et al 2017). The purpose of this article is to review the development of numerical simulations of EPBs over the past 40 years and discuss a possible future research direction involving the use of state-of-the-art numerical models toward the evaluation and forecast of ionospheric scintillations.…”
Section: Introductionmentioning
confidence: 99%
“…This explanation is appealing because there is a physical basis for this asymmetry. That is, west-wall structuring may be produced by an interchange instability, driven by an eastward neutral wind [Tsunoda, 1983], or structuring could be associated with a velocity shear in F region plasma [Yokoyama et al, 2015].…”
Section: East-west Asymmetriesmentioning
confidence: 99%